(untitled) - Heppner, P. Paul (Belmont, CA, 2008)
With enlightening examples and illustrations drawn from the counseling literature, "Research design in counseling" fully addresses the most common issues that counseling researchers encounter. The authors' accessible approach provides you with an understanding of the various types of research, including both quantitative and qualitative approaches. Filled with helpful examples that draw from a broad variety of research designs, this book provides the fundamentals of conducting research while providing clear instruction on writing and publishing the research report.
Keywords: Counseling; Research,Methodology